Analisis Kualitatif Pewarna Rhodamin B Pada Terasi Dengan Metode Kromatografi Lapis Tipis - Muawanah Muawanah; Dewi Arisanti; Abdul Razak; Nur Qadri Rasyid (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2023)
Shrimp paste is one of the fishery products obtained by a fermentation process, and the main ingredients are both small shrimp and fish. In the production of shrimp paste, traders sometimes add prohibited dyes such as rhodamin B, according to the Minister of Health of the Republic of Indonesia, Number 239/Menkes/Per/V/85, because it is a synthetic dye for paper, textiles, and ink. Rhodamin B can cause liver function disorders and cause cancer. When used in food products. This study aims to determine the presence of rhodamin B dye in shrimp paste. The sampling technique was purposive sampling, with a total of 10 samples. This study conducted a qualitative analysis of rhodamin B dye using the Thin Layer Chromatography (TLC) method. Based on the results of the study, 10 samples were obtained, namely 6 positive shrimp paste samples containing rhodamin B dye, as seen based on the stains and Rf value of the sample and the rhodamin B standard. It can be concluded that most of the shrimp paste samples contain rhodamine B dye.